Community empowerment through training on healthy carrot-based brownies - Karini, Tri Addya; Arfah, Nur Hasanah; Ridhayanti, Ridhayanti; Sudarsin, Muhammad (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Carrots are the main vegetable and are very loved because of their fresh and sweet taste and very diverse content. The efficacy of carrots that have been studied with this content is that it can help reduce high blood pressure. The purpose of this dedication is to conduct training in making healthy carrot-based brownies. The method used in this training is a direct practice method. Based on the results of data collection on the number of participants who participated in the training, which was as many as 30 respondents and the concept carried out was to make a video of the process of making carrot-based brownies and then broadcast using LCD, then given posters about the steps to make brownies, and practice directly at residents' homes. Based on the results of this study, it can be concluded that the quality of brownies with carrot mixture is quite satisfactory in terms of colour, taste, aroma, and texture. The people of Bontolebang Hamlet, Kanreapia Village were very enthusiastic when we conducted training and practice in making carrot-based brownies